The making of the Chinese Civil Code : promises and persistent problems / edited by Hao Jiang, Pietro Sirena. - Jiang, Hao (Law teacher); Sirena, Pietro (Cambridge University Press, 2023)
The Chinese Civil Code (2020) is the first ever Civil Code in mainland China since 1949. In addition to the consolidation of existing civil legislations, the Code incorporated a number of doctrinal and structural changes that are significant both in and beyond China. The chapters in this volume demonstrate the extent of European influence in Chinese Civil Law and also shows how Chinese law innovates upon those influences. The book shares the insights from both the key Chinese scholars who were directly involved in the drafting process and veteran Western scholars who study Chinese private law.